An Energy Efficient Multihop Routing Protocol for Wireless Sensor Networks - Kaur, Charanpreet; Chhabra, Amit (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor networks comprise of numerous sensor nodes which are randomly distributed in an observing region. These nodes are not only supervised the surrounding but also gathered the data from it. Various routing protocols have been aimed for wireless sensor networks to effective and efficient utilization of energy since SNs are powered with limited and non-rechargeable batteries. In this paper, an enhanced version of K-LEACH routing protocol is proposed i.e. Multihop K-LEACH to minimize the power depletion for WSNs. The proposed technique utilizes the k-medoid clustering method to uniform clustering of nodes and multihop routing approach to reduce the power depletion, which leads to prolonging the lifespan of network. The performance of the proposed technique is compared with K-LEACH using NS2. The simulation shows the better results of multihop K-LEACH over the previous technique.